EFFICIENCY ANALYSIS OF CONVENTIONAL BANKS AND ISLAMIC BANKS BEFORE AND DURING COVID-19 - Silvia Dwi Aryanti; Edy Yusuf Agung Gunanto (Universitas Airlangga, 2022)
This study aims to analyze the efficiency level of conventionalcommercial banks and Islamic commercial banks in Indonesia fromthe first quarter of 2018 - the fourth quarter of 2020. This researchperiod is third year with the data used are 12 commercial banks anduses a quantitative approach. The method used in this research isStochastic Frontier Analysis (SFA). The results of this study are thatconventional commercial banks are more efficient than Islamiccommercial banks both before the COVID-19 pandemic and duringthe COVID-19 pandemic, more over there are differences in efficiencybetween conventional commercial banks and Islamic commercialbanks.